HELENE HUDSON ARTICLE: Supporting First Nations, Inuit and Métis (FNIM) in an oncology setting—My experience as a FNIM Nurse Navigator - Carolyn Roberts; Gwen Barton; Allyson McDonald (Pappin Communications, 2020)
I spent my youth and a great deal of my nursing practice in a remote region on Québec’s Lower North Shore. As a nurse responsible for populations of 600 residents or less I have endured my fair share of precarious experiences. Outpost clinics are significantly different than mainstream health centres. There are no labs, x-rays, ultrasounds and, at times, no doctor. Nurses are the community’s life support. When emergencies arise they rarely occur within the clinic. Transporting patients to hospital can be extremely challenging. However, there is a strong sense of community through each village in this region. Community members can be your biggest asset in recovering injured or sick patients. They are your right hand and sometimes your only extra hands. From transporting patients by snowmobile and komatik in the winter to a stretcher in the back of my own van in the summer, I have learned how to develop a makeshift style of nursing.